The Effect of Glutamatergic Modulators on Extracellular Glutamate: How Does this Information Contribute to the Discovery of Novel Antidepressants? - Marcos Emilio Frizzo, PhD (Elsevier, 2019)
ABSTRACT: Background: In the search for new antidepressants, clinical researchers have been using drugs that simultaneously modulate multiple targets. During preclinical and clinical trials, the glutamatergic modulators riluzole and ketamine have received particular attention. Glutamatergic agents have a modulatory effect on synaptic transmission, so they can act on both neurons and astrocytes. In addition to influencing the quantity of glutamate released, these modulators can also affect the expression, localization, and functionality of glutamate-binding sites. Objective: This review discusses the complexity of the glutamatergic system, the ambiguity of data regarding glutamate levels in patients with depression, as well as the mechanisms of action for riluzole and ketamine, which includes their relation to the physiology of glutamatergic transmission. The principal aim is to contribute to the development of novel glutamatergic antidepressant medications whilst emphasizing the need for innovative approaches that evaluate their effects on extracellular glutamate. Methods: Literature was obtained via PubMed by searching the term depression in combination with each of the following terms: riluzole, ketamine, and glutamate. The search was restricted to full-text articles published in English between 1985 and 2018 relating to both the modulatory mechanisms of glutamatergic-binding proteins and the antidepressant actions of these medicines. Articles about mechanisms associated with synaptic plasticity and antidepressant effects were excluded. Results: Although experimental data relates glutamatergic signaling to the pathophysiology of major depression and bipolar disorder, the role of glutamate-as well as its extracellular concentration in patients with said disorders-is still unclear. Riluzole's antidepressant action is ascribed to its capacity to reduce glutamate levels in the synaptic cleft, and ketamine's effect has been associated with increased extracellular glutamate levels. Conclusions: The strategy of using glutamatergic modulators as therapeutic agents requires a better understanding of the role of glutamate in the pathophysiology of depression. Gaining such understanding is a challenge because it entails evaluating different targets as well as the effects of these modulators on the kinetics of glutamate uptake. Essentially, glutamate transport is a dynamic process and, currently, it is still necessary to develop new approaches to assay glutamate in the synaptic cleft. ORCID: 0000-0002-3358-6939. Keywords: Depression, Glutamate, Glutamate uptake, Ketamine, Kir4.1 channel, Riluzole